2016
DOI: 10.1007/s13277-016-5163-2
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory microenvironment in epithelial ovarian cancer: a role for TLR4 and MyD88 and related proteins

Abstract: The tumor-associated inflammatory microenvironment may play a pivotal role in epithelial ovarian cancer (EOC) carcinogenesis and outcomes, but a detailed profile in patient-derived tumors is needed. Here we investigated the expression of TLR4- and MyD88-associated markers in tumors from over 500 EOC patients using immunohistochemical staining. We demonstrate that high expression of TLR4 and MyD88 predicts poorer overall survival in patients with EOC; most likely, this is due to their association with serous hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 25 publications
4
40
0
2
Order By: Relevance
“…While genetic models of the development of ovarian cancer in the fallopian tube exist (25,26), the ID8 model is one of very few routinely available syngeneic murine models of ovarian cancer (27) that can be transplanted into immunocompetent mice and creates an immunosuppressed tumor microenvironment (22), making it well suited to our studies. Parental ID8 cells (21) were modified to overexpress VEGF and Defensin (18,20) to make them more aggressive and more like some human ovarian cancers (28,29). The ID8-VEGF-Defensin cells also consistently generate hemorrhagic ascites ∼4 wk after transplantation of only 250,000 cells.…”
Section: Resultsmentioning
confidence: 99%
“…While genetic models of the development of ovarian cancer in the fallopian tube exist (25,26), the ID8 model is one of very few routinely available syngeneic murine models of ovarian cancer (27) that can be transplanted into immunocompetent mice and creates an immunosuppressed tumor microenvironment (22), making it well suited to our studies. Parental ID8 cells (21) were modified to overexpress VEGF and Defensin (18,20) to make them more aggressive and more like some human ovarian cancers (28,29). The ID8-VEGF-Defensin cells also consistently generate hemorrhagic ascites ∼4 wk after transplantation of only 250,000 cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, HMGB1 is increased in ovarian, colorectal, lung and gastric cancer, indicating that HMGB1 is an important mediator for cancer transformation, proliferation and invasion (7,8,10). Furthermore, it has recently been demonstrated that activation of TLR4/NF-κB signaling by DAMPs may contribute to an inflammatory microenvironment that drives a more aggressive phenotype with poorer clinical outcomes in patients with MEOC (11,18). Wang et al (3) performed a meta-analysis that revealed that HMGB1 levels in the tissue and serum of patients with OC are significantly higher compared with those detected in benign tumor and normal ovarian samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high HMGB1 expression is associated with poor differentiation, a high stage and a positive lymph node status in OC (10). Toll-like receptors (TLRs) are essential components of innate immunity that enhance the function of HMGB1 in cancer, by creating a procancerous environment through inflammation, angiogenesis and cell death (11). As an important damage-associated molecular pattern (DAMP), HMGB1 activation of TLRs expressed on tumor cells initiates pro-inflammatory signaling pathways and mediates the release of cytokines and chemokines from tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Their release from cancerous cells to the extracellular medium promotes tumor growth and metastasis, and their overexpression is associated to ovarian cancer, among others [ 3 ]. Increased HMGB1 expression has been associated to TLR4 expression and activated NF-κB signaling pathway [ 4 , 5 ]. This is accompanied by worse clinical outcomes in EOC patients, which suggests that signaling by endogenous ligands may contribute to an inflammatory microenvironment, which worsens the disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased HMGB1 expression has been associated to TLR4 expression and activated NF-κB signaling pathway [ 4 , 5 ]. This is accompanied by worse clinical outcomes in EOC patients, which suggests that signaling by endogenous ligands may contribute to an inflammatory microenvironment, which worsens the disease [ 4 ]. In the ovarian cancer cell line SKOV-3, HMGB1 silencing diminishes the expression of VEGF and CXCL12, revealing its involvement in angiogenesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%